Liouville-type results for the Lane-Emden equation - Alberto Roncoroni (Bruno Pini Mathematical Analysis Seminar, 2023)
We present some Liouville-type result for the Lane-Emden equation in the subcritical and in the critical regimes. In particular, we focus on the so-called critical p-Laplace equation.